From the Discipline of Law, a Frontier for Psychiatric Rehabilitation - Ferrazzi, Priscilla (International Journal of Psychosocial Rehabilitation, 2018)
While largely unknown to the field of psychiatric rehabilitation, therapeutic jurisprudence emerged from the separate discipline of law as a theoretical approach that maximizes the law’s potential for therapeutic outcomes and provides a “philosophic foundation” for criminal court responses to people with mental ill- ness. Although a rehabilitative response is its key animating principle, therapeutic jurisprudence was de- veloped with little reference to—or mutual benefit from—psychiatric rehabilitation. This paper describes the legal concept of therapeutic jurisprudence and criminal court mental health initiatives from the per- spective of psychiatric rehabilitation. It argues that these developments represent an interdisciplinary op- portunity for psychiatric rehabilitation.